2021
DOI: 10.12688/wellcomeopenres.16572.1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the 6-phosphogluconate dehydrogenase from Gluconobacter oxydans reveals tetrameric 6PGDHs as the crucial intermediate in the evolution of structure and cofactor preference in the 6PGDH family

Abstract: Background: The enzyme 6-phosphogluconate dehydrogenase (6PGDH) is the central enzyme of the oxidative pentose phosphate pathway. Members of the 6PGDH family belong to different classes: either homodimeric enzymes assembled from long-chain subunits or homotetrameric ones assembled from short-chain subunits. Dimeric 6PGDHs bear an internal duplication absent in tetrameric 6PGDHs and distant homologues of the β-hydroxyacid dehydrogenase (βHADH) superfamily. Methods: We use X-ray crystallography to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Until recently, it was generally assumed that the oxidative branch of the pentose-phosphate pathway was absent in most of the archaeal organisms studied since homologs of classical bacterial G6PDH could not be identified in any archaeon, and a modified version of this pathway was proposed (Soderberg, 2005). Nevertheless, to date, the presence of G6PDH as well as 6-phosphogluconate dehydrogenase has been reported in Haloabacteria, Pacearchaeota, Thaumarchaeota, and Asgarchaeota organisms (Maturana et al, 2021), although SDR-G6PDH seems to be restricted to Halobacteria, as has been shown previously by Pickl and Schönheit (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it was generally assumed that the oxidative branch of the pentose-phosphate pathway was absent in most of the archaeal organisms studied since homologs of classical bacterial G6PDH could not be identified in any archaeon, and a modified version of this pathway was proposed (Soderberg, 2005). Nevertheless, to date, the presence of G6PDH as well as 6-phosphogluconate dehydrogenase has been reported in Haloabacteria, Pacearchaeota, Thaumarchaeota, and Asgarchaeota organisms (Maturana et al, 2021), although SDR-G6PDH seems to be restricted to Halobacteria, as has been shown previously by Pickl and Schönheit (2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that there are both homodimeric and homotetrameric 6PGDHs. The latter group are mainly found in prokaryotes, although a dimer-tetramer equilibrium affected by ligands has been reported for 6PGDH from the protist Trypanosoma brucei (Tsai & Chen, 1998;Hanau et al, 2013;Maturana et al, 2021;Sarmiento-Pavı ´a et al, 2021).…”
Section: Different Types Of 6pgdhmentioning
confidence: 97%
“…Some bacterial 6PGDHs are specific for NAD + , while others can use both NAD + and NADP + (Maturana et al, 2021). In the thermostable 6PGDH from the hyperthermophilic bacterium Thermotoga maritima the coenzyme preference could be reversed from NADP + to NAD + by site-directed topical reviews Acta Cryst.…”
Section: Different Types Of 6pgdhmentioning
confidence: 99%
See 2 more Smart Citations